THE CORRELATION BETWEEN PERSONALITY DISORDERS IN SECOND-YEAR FEMALE STUDENTS AND THEIR PERFORMANCE IN SELECTED FLOOR EXERCISES IN ARTISTIC GYMNASTICS - Athraa Hamzah Oudah (Proximus Journal Publishing, 2024)
The study intends to ascertain the disturbed personality of female students in their second and third year at Al-Mustansiriya University's College of Basic Education, Department of Physical Education and Sports Science, as well as the degree to which these students perform in certain floor exercises in accordance with their disturbed personalities. Understanding the connection between the research sample's performance on floor exercises and troubled personalities is another goal of the study. The researcher employed survey and correlational approaches in conjunction with the descriptive method, which she thinks to be consistent with her research criteria and effective in accomplishing the study's goals.
Keywords: criteria; effective; approaches